2011
DOI: 10.3354/dao02316
|View full text |Cite
|
Sign up to set email alerts
|

Antemortem diagnosis of a ventricular septal defect in a California sea lion Zalophus californianus

Abstract: A yearling California sea lion Zalophus californianus stranded in poor body condition, and on physical examination a heart murmur was audible bilaterally. The sea lion was diagnosed with a left-to-right shunting membranous ventricular septal defect (VSD) using B-mode, color-flow Doppler and continuous-wave Doppler echocardiography. A left-to-right intracardiac shunting lesion was confirmed during cardiac angiographic computed tomography. The VSD defect was verified during the necropsy examination. On histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Cardiac abnormalities and diseases have been reported postmortem in marine mammals such as northern elephant seals (Mirounga angustirostris), pygmy sperm whales (Kogia breviceps), bottlenose dolphins (Tursiops truncatus), northern fur seals (Callorhinus ursinus), dwarf sperm whales (Kogia sima), Florida manatees (Trichechus manatus latirostris), and southern sea otters (Enhydra lutris) (Trupkiewicz et al, 1997;Kreuder et al, 2003;Bossart et al, 2007;Powell et al, 2009;Spraker & Lander, 2010;Gerlach et al, 2013). Only a few studies have achieved the in vivo diagnosis of heart abnormalities in marine mammals through echocardiography such as the foramen ovale and ductus arteriosus patency found in neonatal harbor seals (Phoca vitulina; Dennison et al, 2011a) or the ventricular septal defects found in a harbor porpoise (Phocoena phocoena; Szatmári et al, 2016) and California sea lions (Zalophus californianus; Dennison et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac abnormalities and diseases have been reported postmortem in marine mammals such as northern elephant seals (Mirounga angustirostris), pygmy sperm whales (Kogia breviceps), bottlenose dolphins (Tursiops truncatus), northern fur seals (Callorhinus ursinus), dwarf sperm whales (Kogia sima), Florida manatees (Trichechus manatus latirostris), and southern sea otters (Enhydra lutris) (Trupkiewicz et al, 1997;Kreuder et al, 2003;Bossart et al, 2007;Powell et al, 2009;Spraker & Lander, 2010;Gerlach et al, 2013). Only a few studies have achieved the in vivo diagnosis of heart abnormalities in marine mammals through echocardiography such as the foramen ovale and ductus arteriosus patency found in neonatal harbor seals (Phoca vitulina; Dennison et al, 2011a) or the ventricular septal defects found in a harbor porpoise (Phocoena phocoena; Szatmári et al, 2016) and California sea lions (Zalophus californianus; Dennison et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The VSD to date has been described in several domesticated (Hamlin and others , Halnan , Knauer and others , Hawe , Donnelly and others , Vörös and others ) and non‐domesticated animals (Cook and others , Shinohara and Nishimura , Swindle and others , Johnson and others , Binhazim and others , Boon and others , Moore and others , Suedmeyer and others , Koie and others , Dennison and others ), including avian (Einzig and others , Harari and Miller , Bailey and Kinne ) and reptile (Brockman and Kennedy, ) species. In dogs, VSD has been found in conjunction with other cardiac defects in almost half of the cases (48%), usually pulmonic stenosis (65%)(Oliveira and others ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac anomalies have been previously reported in marine mammals (Gray & Conklin 1974, Dennison et al 2011. Poor maternal condition, in utero viral infection, or exposure to toxin, as well as chromosomal and genetic alterations have been suggested as possible causes that are well described in humans (Schoen & Mitchell 2010).…”
Section: Non-infectious Diseasementioning
confidence: 99%